Mathematical modelling the emergence of viruses in naïve populations - Fairbanks, Emma Louise (2022)
Viruses pose a global threat to both humans and other animals. The severity of this impact is often amplified in populations with no prior immunity to the virus. Epidemics in naïve populations may occur due to novel virus emergence or the emergence of a known virus in a new geographical region. With climate change and globalisation, the frequency of the epidemics is likely to increase. Vector-borne viruses, spread by insects, have been increasingly observed in geographical regions where it was once believed that climatic conditions would not support the spread of these viruses. Mathematical models are a useful tool for policy makers to refer to while attempting to control and prevent epidemics. First, we focus on the Culicoides-borne virus African horse sickness virus (AHSV), using a systematic search to further the understanding of the dynamics of infection in naïve equines and parameterising a spatio-temporal model for the emergence of AHSV in naïve equids in Morocco 1998. Secondly, we apply mathematical and statistical models to study severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in universities.